Biodegradable Redox‐Responsive AIEgen‐Based‐Covalent Organic Framework Nanocarriers for Long‐Term Treatment of Myocardial Ischemia/Reperfusion Injury. Issue 47 (17th October 2022) - Huang, Chenguang; Zhou, Shengnan; Chen, Chen; Wang, Xiaoyu; Ding, Rui; Xu, Yinshuang; Cheng, Ziwei; Ye, Zhuqing; Sun, Lijun; Wang, Zi‐jian; Hu, Danyou; Jia, Xudong; et al.
Abstract: Timely restoration of blood supply after myocardial ischemia is imperative for the treatment of acute myocardial infarction but causes additional myocardial ischemia/reperfusion (MI/R) injury, which has not been hitherto effectively targeted by interventions for MI/R injury. Hence, the development of advanced nanomedicine that can reduce apoptosis of cardiomyocytes while protecting against MI/R in vivo is of utmost importance. Herein, a redox‐responsive and emissive TPE‐ss covalent organic framework (COF) nanocarrier by integrating aggregation‐induced emission luminogens and redox‐responsive disulfide motifs into the COF skeleton is developed. TPE‐ss COF allows for efficient loading and delivery of matrine, a renowned anti‐cryptosporidial drug, which significantly reduces MI/R‐induced functional deterioration and cardiomyocyte injury when injected through the tail vein into MI/R models at 5 min after 30 min of ischemia. Moreover, TPE‐ss COF@Matrine shows a drastic reduction in cardiomyocyte apoptosis and improvements in cardiac function and survival rate. The effect of the TPE‐ss COF carrier is further elucidated by enhanced cardiomyocyte viability and triphenyltetrazolium chloride staining in vitro. This work demonstrates the cardioprotective effect of TPE‐ss COFs for MI/R injury, which unleashes the immense potential of using COFs as smart drug carriers for the peri‐reperfusion treatment of ischemic heart disease with low cost, high stability, and single postoperative intervention. Abstract : A simple strategy is designed for the construction of a redox‐responsive emissive AIEgen‐based covalent organic framework (COF) as an effective drug‐delivery carrier for the anti‐cryptosporidial drug matrine. This work represents an example of using a redox‐responsive emissive COF as a drug delivery carrier for MI/R treatment, which opens an avenue for the efficient treatment of ischemic heart disease.